Advancing Inclusive Legal Frameworks at the Local Level: The Sibolga City Council’s Initiative on Disability Rights Protection - Depi Safitri; Muhammad Syukran Yamin Lubis (Abdurrauf Law and Sharia, 2026)
This research aims to analyze the initiative of the Regional People's Representative Council (DPRD) of Sibolga City in the formation of the Regional Regulation concerning the Protection and Fulfillment of the Rights of Persons with Disabilities, focusing on two main issues: the authority of the Sibolga City DPRD in initiating Regional Regulations and the actual process of its formation. Persons with disabilities in Sibolga City require a local legal framework as an implementation of Law Number 8 of 2016 to guarantee their fundamental rights. The research method employed is empirical legal research with data collection techniques through direct observation and literature study of relevant legal documents. The results indicate that the Sibolga City DPRD possesses attributive authority based on Law Number 23 of 2014 and Government Regulation Number 12 of 2018 to independently propose draft regional regulations to fill local legal vacuums. The formation process is carried out systematically through the stages of planning, drafting, and plenary discussions. A crucial point in this process is the strategic collaboration between the Sibolga City DPRD and academic institutions in drafting the Academic Paper to ensure that the resulting regulation is scientifically sound and implementable for the people of Sibolga City. [Penelitian ini bertujuan untuk menganalisis inisiatif Dewan Perwakilan Rakyat Daerah (DPRD) Kota Sibolga dalam pembentukan Peraturan Daerah tentang Perlindungan dan Pemenuhan Hak-Hak Penyandang Disabilitas, dengan fokus pada dua isu utama: kewenangan DPRD Kota Sibolga dalam memulai Peraturan Daerah dan proses aktual pembentukannya. Penyandang disabilitas di Kota Sibolga membutuhkan kerangka hukum lokal sebagai implementasi Undang-Undang Nomor 8 Tahun 2016 untuk menjamin hak-hak fundamental mereka. Metode penelitian yang digunakan adalah penelitian hukum empiris dengan teknik pengumpulan data melalui observasi langsung dan studi literatur dokumen hukum yang relevan. Hasil penelitian menunjukkan bahwa DPRD Kota Sibolga memiliki kewenangan berdasarkan Undang-Undang Nomor 23 Tahun 2014 dan Peraturan Pemerintah Nomor 12 Tahun 2018 untuk secara mandiri mengusulkan rancangan peraturan daerah guna mengisi kekosongan hukum lokal. Proses pembentukan dilakukan secara sistematis melalui tahapan perencanaan, penyusunan, dan diskusi pleno. Poin penting dalam proses ini adalah kolaborasi strategis antara DPRD Kota Sibolga dan lembaga akademis dalam menyusun Makalah Akademis untuk memastikan bahwa peraturan yang dihasilkan berlandaskan ilmiah dan dapat diterapkan bagi masyarakat Kota Sibolga.]